Sustainable Development and its Implications for Student Welfare - Tony Margiyanto Adi; Cicih Ratnasih (PT. ALHAFI BERKAH INDONESIA, 2025)
This research examines the relationship between sustainable development practices in educational institutions and their impact on student welfare. Using a qualitative approach through interviews and observations in five secondary schools, this study identifies that the implementation of sustainable principles in school design, curriculum, and daily operations correlates positively with improved physical and mental well-being of students. The findings indicate that learning environments that apply sustainability principles create an atmosphere that supports students' socio-emotional development, increases environmental awareness, and facilitates effective learning processes. This study recommends further integration of sustainable practices in the education system as a strategy to improve overall student welfare.